Recent Advances in Systems Safety and Security - Pricop, Emil; Stamatescu, Grigore (Studies in Systems, Decision and Control,, 2016)
This book represents a timely overview of advances in systems safety and security, based on selected, revised and extended contributions from the 2nd and 3rd editions of the International Workshop on Systems Safety and Security - IWSSS, held in 2014 and 2015, respectively, in Bucharest, Romania. It includes 14 chapters, co-authored by 34 researchers from 7 countries. The book provides an useful reference from both theoretical and applied perspectives in what concerns recent progress in this area of critical interest. Contributions, broadly grouped by core topic, address challenges related to information theoretic methods for assuring systems safety and security, cloud-based solutions, image processing approaches, distributed sensor networks and legal or risk analysis viewpoints. These are mostly accompanied by associated case studies providing additional practical value and underlying the broad relevance and impact of the field.